Automating Endoscope Motion in Robotic Surgery: A Usability Study on da Vinci-Assisted Ex Vivo Neobladder Reconstruction - Da Col, Tommaso; Caccianiga, Guido; Catellani, Michele; Mariani, Andrea; Ferro, Matteo; Cordima, Giovanni; De Momi, Elena; Ferrigno, Giancarlo; de Cobelli, Ottavio (Frontiers in Robotics and AI, 2021)
Robots for minimally-invasive surgery introduces many advantages, but still requires the surgeon to alternatively control the surgical instruments and the endoscope. This work aims at providing autonomous navigation of the endoscope during a surgical procedure. The autonomous endoscope motion was integrated with the daVinci research kit and a feasibility study was conducted by 10 urologists. They carried out an ex-vivo orthotopic neobladder reconstruction twice, using both traditional and autonomous control. The new method was assessed by analyzing the total procedure time and the time spent with the instruments out of the field of view. Moreover, the subjective opinions of the users were collected by using a system usability scale. The average total procedure time with autonomous endoscope navigation was comparable to the classic control (p=0.85>0.05), yet it significantly reduced the time out of the field of view (p=0.022<0.05). The average system usability score overcame the threshold usually identified as the limit to assess good usability (average score=73.25>68). Based on our findings, the autonomous endoscope improves the usability of the surgical system and it has the potential to be an additional and customizable tool for the surgeon that can always take control of the endoscope or leave it move autonomously.